2009
DOI: 10.1016/j.neuron.2009.11.028
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges Natural Images Pose for Visual Adaptation

Abstract: Advances in our understanding of natural image statistics and of gain control within the retinal circuitry are leading to new insights into the classic problem of retinal light adaptation. Here we review what we know about how rapid adaptation occurs during active exploration of the visual scene. Adaptational mechanisms must balance the competing demands of adapting quickly, locally, and reliably, and this balance must be maintained as lighting conditions change. Multiple adaptational mechanisms in different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
227
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(232 citation statements)
references
References 75 publications
4
227
0
1
Order By: Relevance
“…In the visual system, gain modulation adjusts neural responsiveness without impairing selectivity and is used to scale cortical network function in a contrast-dependent manner (33). Changes in input-output functions adjust firing rates to enhance coding of dynamic visual scenes where luminance, spatial frequency, and contrast often change over many orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…In the visual system, gain modulation adjusts neural responsiveness without impairing selectivity and is used to scale cortical network function in a contrast-dependent manner (33). Changes in input-output functions adjust firing rates to enhance coding of dynamic visual scenes where luminance, spatial frequency, and contrast often change over many orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The visual system shows exact adaptation, as evidenced by experiments that track the eyes and accordingly move the visual field to cancel out these rapid eye movements, rendering the viewer unable to discern contrast within seconds (25)(26)(27). Vision also shows Weber's law to a good approximation across three decades of stimuli (28,29). Because vision exhibits both exact adaptation and Weber's law, it might also show FCD, a hypothesis that is experimentally testable.…”
Section: Fcd Entails Exact Adaptation and Weber's Law But Is Not Guarmentioning
confidence: 99%
“…Regarding mechanisms, the spatiotemporal linear filter of the LN model is typically interpreted as mapping onto the aggregate sequential mechanisms of phototransduction, signal filtering and transmission through bipolar and amacrine cell pathways, and summation at the ganglion cell, while the nonlinearity is mapped onto the spiking threshold of ganglion cells. Regarding accuracy, while previous studies have found that these simple models can, for some neurons, capture most of the variance of the responses to low-resolution spatiotemporal white noise [9, 12, 20], they do not describe responses to stimuli with more structure such as natural scenes [13, 3033]. …”
Section: Introductionmentioning
confidence: 99%